Validasi Metode Bioautografi untuk Determinasi Kloramfenikol - Susanti, Meliana; Isnaeni, .; Poedjiarti, Sri (Jurnal Kedokteran Indonesia, 2009)
Background: Contact bioautography method has been developed for determination of chloramphenicol concentration. Validation of bioautography method has beed carried out by using parameters including linearity, accuracy, precision, and detection limit.Methods: Thin Layer Chromatography of chloramphenicol has been performed by using Silica gel 60 F254 as a stationary phase, chloroform : methanol (80:20, v/v) and UV lamp as a solvent and for spot visualization respectively. Before spotting, analyte of the chloramphenicol was dissolved in aceton as solvent. Bioautography has been performed by using Escherichia coli ATCC 25922 as a bacterial and Nutrient Agar as medium test.Results: It was found that one spot visualized on the chromatogram has Rf value 0.5. The result showed that respon of activity to be linear at the amount of chloramphenicol between 100 ppm-200 ppm, with regression quotion: Y = 2.8X - 4.3, r value =0.9 and Vxo = 1.8%. Accuracy and precision of the method are 2.8% + 2.3 and 96.2% + 4.7 respectively.Conclusion: Detection Limit (DL) value is 0.06 Î¼g could be expressed as Minimum Inhibition Concentration (MIC). Jurnal Kedokteran Indonesia: 1 (1): 15-24Keywords: chloramphenicol, bioautography, Validation method